O sistema de vigilância alimentar e nutricional entre o preconizado e o realizado: percepções de usuários, profissionais de saúde e gestores - Pinto, Maria Soraia (2023)
Food and Nutritional Surveillance (FNS) encompasses continuous data collection and analysis activities whose purpose is to enable the routine evaluation and organization of nutritional care in the Unified Health System (UHS), identifying priorities according to the population's food and nutrition situation. The objective is to understand the perception of managers, health professionals and users about the use and quality of data proposed in SISVAN in different Brazilian states. This is a qualitative approach study that is part of the multicenter research “Perspectives and challenges of improving the Food and Nutritional Surveillance System: a mixed methods approach”. The team for this project consisted of nutritionists, nurses and physicians with higher education, specialists in public health, nursing and psychology. The information collection team received theoretical and practical training to standardize the procedures prior to the interviews. Data collection took place from September 2020 to June 2022, which coincided with the COVID-19 pandemic period. The scenarios were the Basic Health Units (BHU) of the following cities: Cuiabá (MT), Fortaleza (CE), Novo Hamburgo (RS), Rio Branco (AC) and Niterói (RJ). In each municipality, two UHS were selected, one located in a neighborhood with a low Human Development Index (HDI) and the other in a neighborhood with a high HDI, to enable an assessment of different socioeconomic contexts. From the analyzed research material, it was possible to establish 1 theme for users: lack of knowledge about SISVAN actions, for professionals four themes: 1. (Mis) knowledge about SISVAN; 2. SISVAN and income transfer; 3. Difficulties in implementation and use and 4. Potentialities of SISVAN. For managers, two themes 1. Between what is recommended and what is achieved and 2. Reality to be transformed. Lack of knowledge about SISVAN and its actions and/or its limited understanding emerged as the main obstacle to its operation, interfering with its proper execution, use and data quality. Disagreements and reunions were identified regarding knowledge and (in)comprehensions about the system, users are still on the sidelines of the process and therefore do not have their nutritional diagnoses shared with the different actors involved and especially do not take ownership of self-care. This study points out some assumptions to be observed and worked on for the operationalization of a system that proposes to be universal, as it should describe the nutritional profile of all users who seek care in the PHC and thus allow the dissemination of information to society as a whole. Making SISVAN more operational also involves strengthening the SUS and the PHC, which have been seriously threatened in recent years, due to changes in the economic and political context in Brazil, aggravating a scenario full of inequalities and restriction of the population's rights.